Enhanced osteogenesis by addition of cancellous bone chips at xenogenic bone augmentation: In vitro and in vivo experiments. Issue 1 (12th November 2022) - Chen, Xiaofan; Wang, Haicheng; Wang, Yuning; Shi, Ying; Wang, Zuolin
Abstract: Objectives: To investigate and compare the influence of deproteinized bovine bone mineral (DBBM) combined with autologous cortical (CorBC) or cancellous bone chips (CanBC) as bone grafts on guided bone regeneration (GBR) in vivo and in vitro. Materials and Methods: Defects were created in the mandibular buccal alveolar ridges in dogs and randomly filled with 3 groups of bone grafts: DBBM, DBBM + CorBC, or DBBM + CanBC. Osteogenesis was evaluated by sequential fluorescent labeling and histological analysis. Moreover, rat bilateral calvaria defects were randomly grafted with DBBM, DBBM + CorBC, or DBBM + CanBC. A blank group was included as control. Defect healing was assessed by histological staining, micro‐CT, and quantitative polymerase chain reaction. In vitro migration, proliferation, and osteogenic differentiation assays were performed by stimulating rat bone marrow mesenchymal stem cells (rBMSCs) with cortical (CorBCM) or cancellous bone conditioned medium (CanBCM) to unveil the cellular mechanism. Results: In the canine model, the augmented sites of DBBM + CanBC exhibited higher mineralized tissue proportion than the other two groups (DBBM: 0.61 ± 0.03 versus DBBM + CorBC: 0.69 ± 0.07 versus DBBM + CanBC: 0.86 ± 0.06; p  < .05). In the rat model, the BV/TV value of DBBM + CanBC (0.51 ± 0.01) was higher than those of DBBM + CorBC (0.41 ± 0.02), DBBM (0.31 ± 0.01), and Control (0.10 ± 0.01; p  < .01). Further radiological, histological and transcriptional results showed similar trends. In vitro experiments revealed that CorBCM and especially CanBCM could enhance rBMSCs migration, proliferation, and osteogenic differentiation. Conclusion: In vivo and in vitro experiments verified favorable synergistic effect of mixing autologous bone chips with DBBM on osteogenesis. Furthermore, CanBC presented more powerful osteogenic effect than CorBC.